Model dan Strategi Pendidikan Pondok Pesantren Miftahul Hikmah Parengan Tuban dalam Menghadapi Tantangan Era Globalisasi - Edy Kisyanto (Saintifika Islamica, 2023)
The purpose of this research was to describe how the role of Pondok Pesantren Miftahul Hikmah Sukorejo Parengan Tuban in facing challenges in the globalization era. This is given that the challenges faced by Islamic boarding school educational institutions are getting heavier and more complex. Besides, the orientation of the community in the past with the community is now starting to experience a shift in the impact of the current of globalization. For this reason, pesantren as one of the Islamic educational institutions is expected to be the frontline in answering all challenges in the era of globalization. The existing educational model at Pondok Pesantren Miftahul Hikmah, as well as being a characteristic of this pesantren, including: Sufism -Based Education Model and “Integrated Salafiyah System” Educational Model. The strategies carried out by the Miftahul Hikmah Islamic Boarding School in facing challenges in the era of globalization include making efforts as follows: Selective on social change, improving the quality of teaching staff, renewing pesantren curriculum, renewing learning methods, fostering skills and expertise, and improving facilities and infrastructure.